Perubahan Peran Akuntan Manajemen Dalam Era Berbasis Internet Dengan Usia Sebagai Variabel Moderasi - Suryani, Anita; Ariyanto, Dodik; Dwirandra, Anak Agung Ngurah Bagus; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 32 No 9 (2022)DO - 10.24843/EJA.2022.v32.i09.p04, 2022)
This study aims to examine the effect of the application of Internet-Based Technology (TBI) on the perception of changes in the role of management accountants with user experience, education and age as moderating variables. This research is motivated by the rapid development of TBI which has an impact on the community, including management accountants. The research population is management accountants in Indonesia who are registered at the Indonesian Institute of Management Accountants (IAMI) with a total sample of 110 respondents. Research data is processed with the help of Smart PLS. The implementation of TBI can replace the role of management accountants in several of their functions, roles, tools and activities. Only the age variable has been shown to weaken the influence of the implementation of TBI on changes in the tools and activities of management accountants. Accounting science, both academically and professionally, needs to accommodate accounting staff in the TBI era. Keywords: Internet Based Technology; Perceptions of Changes in Management Accountants; User Experience; Education; Age